(untitled) (Nepalese Journal of Radiology, 2012)
Aim: To study the salient characteristic computed tomographic findings of inflammatory myofibroblastic tumor of lung. Materials and methods: We retrospectively reviewed the CT examinations of twenty histopathologically confirmed cases of inflammatory myofibroblastic tumor of lung and analyzed the involvement, predominant location, pattern of presentation, shape, edge, pattern and degree of enhancement and any atypical findings in those cases. Results: Fourteen cases presented as pulmonary nodules among which twelve as solitary while two cases as multiple pulmonary nodules. Six cases presented as masses. The location was in the parenchyma of the lung among all cases except two masses that were predominantly mediastinal and endobronchial respectively. All nodules demonstrated mild enhancement except one nodule showed moderate and another one marked enhancement. Four masses demonstrated mild enhancement whearas one showed moderate and another marked enhancement. Pleural surface abutting was noticed in one nodule and two masses. Stippled calcification was present in one mass while necrosis was noticed in two other cases that presented as mass. Mass were associated with consolidation in one and as cavity in another case. Conclusion: Although diagnosis of inflammatory myofibroblastic tumor of lung cannot be confirmed radiologically, certain features as presence of nodules or masses that enhance mildly in a patient with equivocal clinical and radiological presentation warrants its inclusion in the differential diagnosis. NJR I VOL 2 I ISSUE 1 18-24 Jan-June, 2012 DOI: http://dx.doi.org/10.3126/njr.v2i1.6974